2017
DOI: 10.1002/open.201600166
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Nitriles to Primary Amines Catalyzed by a Polysilane/SiO2‐Supported Palladium Catalyst under Continuous‐Flow Conditions

Abstract: Hydrogenation of nitriles to primary amines with heterogeneous catalysts under liquid‐phase continuous‐flow conditions is described. Newly developed polysilane/SiO2‐supported Pd was found to be an effective catalyst and various nitriles were converted into primary amine salts in almost quantitative yields under mild reaction conditions. Interestingly, a complex mixture was obtained under batch conditions. Lifetime experiments showed that this catalyst remained active for more than 300 h (TON≥10 000) without lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…19 Illustrating imaginative exploitation of this technology, Saito and co-workers have applied a supported Pd catalyst operating in a continuous ow regime to employ a selective nitrile reduction stage to synthesize the antidepressant drug venlafaxine. 20 In 2016 McMillan and co-workers reported on the hydrogenation of aromatic nitrile compounds over a carbon-supported Pd catalyst. 21 Hydrogenation of benzonitrile to form benzylamine was readily achieved but this was subsequently followed by a hydrogenolysis reaction to produce toluene.…”
Section: Introductionmentioning
confidence: 99%
“…19 Illustrating imaginative exploitation of this technology, Saito and co-workers have applied a supported Pd catalyst operating in a continuous ow regime to employ a selective nitrile reduction stage to synthesize the antidepressant drug venlafaxine. 20 In 2016 McMillan and co-workers reported on the hydrogenation of aromatic nitrile compounds over a carbon-supported Pd catalyst. 21 Hydrogenation of benzonitrile to form benzylamine was readily achieved but this was subsequently followed by a hydrogenolysis reaction to produce toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Nitriles as important chemical materials are widely used in the organic synthesis, for example, as an important source of amino compounds. Newly developed polysilane/SiO 2 ‐supported Pd showed outstanding activity in the hydrogenation of nitriles 61 , as reported by Kobayashi and co‐workers . In their work, two new catalysts were prepared using two supports, that is, Al 2 O 3 and SiO 2 , from DMPSi‐supported Pd catalysts (DMPSi‐Pd).…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%
“…Lifetime experiments showed that this catalyst remained active for more than 300 h (TON>10 000) without loss of selectivity and no metal leaching from the catalyst. In addition, Kobayashi and co‐workers applied this continuous‐flow reaction to the total synthesis of venlafaxine, which is a common antidepressant drug using DMPSi‐Pd/Al 2 O 3 as the catalyst . The hydrogenation step as the key reaction gave the desired compound in 92–93 % yield.…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%
“…† For selectivity enhancement towards the primary amine, both homogeneous and heterogeneous catalysts oen require the use of base additives. 13,[18][19][20]67,68 Remarkably, mild and additive-free conditions can be applied for this highly selective heterogeneous Ru-Triphos system similar to the homogeneous system of Beller and co-workers. 31 When screening the whole supported catalyst library at 100 C and 1.0 mol% catalyst loading, JJ-supported C 2 and PS-bound C 4 performed analogously compared to C 1 (Table 1, entries 4 and 6).…”
Section: Application In Ru-catalyzed Nitrile Reductionmentioning
confidence: 99%
“…13,17 Milder reaction conditions can be applied when utilizing supported Pd catalysts, however, these are still reliant on acidic conditions to produce the terminal amines selectively. [18][19][20] On the other hand, there has been a growing interest to develop highly selective homogeneous catalysts for applications in nitrile reduction under very mild conditions. Most transition-metal complexes are based on precious metals featuring well-dened ligand structures, 17,21,22 but more recently also base metals 23,24 have been employed.…”
Section: Introductionmentioning
confidence: 99%